Nanoscale super-antiskid ceramic tile and preparation method thereof

By preparing a composite coating of cellulose nanocrystal hydrogel and sodium polyacrylate combined with nanoparticles on the surface of ceramic tiles, the problem of anti-slip properties of traditional ceramic tiles in humid environments is solved, achieving a high-performance, low-maintenance anti-slip effect while also possessing a self-cleaning function.

CN119285377AActive Publication Date: 2025-01-10FOSHAN BIHU MARBLE CERAMIC TILE CO LTD

Patent Information

Application Number
CN202411412412.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

Traditional ceramic tiles are not slip-resistant in wet environments, and existing anti-slip treatment methods cannot provide a long-lasting, stable, and low-maintenance solution, while potentially affecting aesthetics or increasing costs.

Method used

A composite coating was prepared by combining cellulose nanocrystal hydrogel, sodium polyacrylate and polylactic acid with nano-sized silica, alumina and titanium dioxide particles. The titanium dioxide nanoparticles were activated by ultraviolet light to form a self-cleaning anti-slip coating.

Benefits of technology

It significantly improves the anti-slip performance of tiles, maintains their aesthetics and durability, provides self-cleaning function, reduces maintenance requirements, and achieves long-lasting anti-slip effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285377A_ABST
    Figure CN119285377A_ABST
Patent Text Reader

Abstract

The invention discloses a nanoscale super-antiskid ceramic tile and a preparation method thereof, and relates to the technical field of ceramic tile production, and the technical scheme is that the preparation method comprises the following steps: S1) preparing a ceramic tile matrix; s2) treating the surface of the ceramic tile; s3) preparing an anti-skid coating; s4) application of the anti-skid coating; s5) surface characteristic adjustment; according to the embodiment of the invention, a unique micro-nano-scale surface structure is formed by using a composite system of the cellulose nanocrystal hydrogel, the sodium polyacrylate mixture, the polylactic acid and the specific nanoparticles, so that excellent anti-skid performance is provided under wet and slippery conditions. And the gamma-methacrylic acid acrylic ester silane is used for carrying out surface modification on the nano particles, so that the nano particle compatibility and stability of the coating are improved, and the long-term durability and the continuous anti-skid effect of the coating are ensured. After the added titanium dioxide nanoparticles are irradiated by ultraviolet rays, the surface of the ceramic tile is endowed with a photocatalytic self-cleaning function, the cleaning and maintenance requirements are reduced, and meanwhile, continuous anti-skid protection is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic tiles, and in particular to a nano-level super-anti-slip ceramic tile and a preparation method thereof. Background Art

[0002] In the building materials industry, especially in the design and manufacture of floor tiles, anti-slip performance has always been an important consideration. With the development of technology, the requirements for the safety, practicality and aesthetics of tile products are also constantly increasing. Traditional tiles, although they have good performance in terms of beauty and durability, often cannot meet the high safety standards of modern buildings in terms of anti-slip performance. Especially in humid environments, such as bathrooms, kitchens, public toilets and outdoor places, the surface of traditional tiles tends to become slippery, increasing the risk of falls and slips.

[0003] There are various methods to solve the anti-slip problem in the current market, including but not limited to applying different textures on the surface of tiles, using tiles with micro-rough surfaces, and coating different anti-slip materials. However, these methods can often only solve the slipping problem to a certain extent, and cannot fundamentally provide a long-term and stable solution. For example, some surface treatment technologies may gradually fail over time and wear and tear from use. In addition, some anti-slip treatments can also have a negative impact on the aesthetics of the tiles, or require complex post-maintenance, adding additional cost burdens. Therefore, the existing technology has obvious deficiencies in providing an anti-slip tile that is both safe and beautiful, while also having low maintenance costs.

[0004] The present invention aims to provide a nano-scale super-anti-slip ceramic tile and a preparation method thereof, which can effectively improve the anti-slip performance of the ceramic tile while maintaining the aesthetics and durability of the ceramic tile. The core technical means include using cellulose nanocrystal (NCC) hydrogel in combination with sodium polyacrylate (PAA) and polylactic acid (PLA), as well as nano-scale silica, alumina and titanium dioxide particles to prepare a composite coating with excellent anti-slip performance. This coating can not only provide anti-slip properties at the microscopic level, but also activate titanium dioxide nanoparticles through ultraviolet (UV) irradiation to give the ceramic tile a self-cleaning function. This preparation method can significantly improve the safety of the ceramic tile without affecting its appearance, and the durability and long-term effectiveness of the coating solve the problems of short-term effects and high maintenance costs of the existing technology. Through this innovative application of nanotechnology, the present invention provides a new solution for the modern building materials industry, meeting the market demand for high-performance and high-safety ceramic tiles. Summary of the invention

[0005] In order to achieve the above-mentioned invention objectives and address the above-mentioned technical problems,

[0006] The present invention provides 1. a method for preparing nano-scale super-anti-slip tiles, comprising the following steps:

[0007] S1) Preparation of ceramic tile substrate;

[0008] S2) Treatment of tile surface;

[0009] S3) Preparation of anti-slip coating;

[0010] S4) Application of anti-slip coating;

[0011] S5) Surface property adjustment.

[0012] Preferably, the preparation of the ceramic tile substrate comprises the following steps:

[0013] Clay, feldspar, quartz sand and kaolin are mixed in a weight ratio of 5 parts, 25 parts, 20 parts and 5 parts, wherein 2 parts of iron oxide colorant and 3 parts of calcium carbonate reinforcing agent are added;

[0014] The mixture was ground into a particle size of 50-100 μm using a ball mill;

[0015] The wet pressing method is adopted, and the pressing is carried out in a hydraulic press;

[0016] The formed tiles were slowly dried in a drying room at 60°C for 12 hours;

[0017] The dried tiles were sintered at 1150°C for 2 hours;

[0018] After firing is complete, allow the tiles to cool naturally to room temperature in the kiln;

[0019] Use 400 grit sandpaper to sand the tile surface.

[0020] Preferably, the treatment of the tile surface comprises the following steps:

[0021] Use 5% NaOH solution to clean the tile surface;

[0022] Rinse the cleaned tile surface with deionized water and dry it;

[0023] Dissolve γ-aminopropyltriethoxysilane (KH550) in ethanol at a volume percentage of 0.5%-1%;

[0024] Evenly apply the above solution on the surface of the tile and dry it naturally at room temperature;

[0025] The coated tile surface was heat cured at 100°C for 1 hour.

[0026] Preferably, the preparation of the anti-slip coating comprises the following steps:

[0027] A cellulose nanocrystal hydrogel (NCC hydrogel) having a solid content of 1-6% (w / w) and a sodium polyacrylate (PAA) solution having a solid content of 0.5-1.5% (w / w) were mixed at a solid content ratio of 1:1;

[0028] Adjusting the pH of the mixture to 7.0;

[0029] Adding 2-6% (w / w) polylactic acid (PLA) to the pH-adjusted mixture;

[0030] Adding 0.5-1.5% (w / w) of nano silicon dioxide particles and 0.5-1.5% (w / w) of nano aluminum oxide particles;

[0031] The nanoparticles were surface modified using 0.1% (w / w) of γ-methacrylate silane (KH570) to improve their compatibility and dispersibility in the hydrogel;

[0032] 0.5-2% (w / w) of titanium dioxide nanoparticles (TiO2) were added to the mixture.

[0033] Preferably, the silicon dioxide nanoparticles have a particle size of 10-30 nanometers, the aluminum oxide nanoparticles have a particle size of 30-50 nanometers, and the titanium dioxide nanoparticles have a particle size of 10-30 nanometers.

[0034] Preferably, the surface modification of the nanoparticles in the anti-slip coating comprises the following steps:

[0035] KH570 was added to isopropanol at a ratio of 0.1% (w / w);

[0036] Nano-silicon dioxide particles and nano-alumina particles are dispersed in deionized water at a ratio of 1% (w / w);

[0037] The above nanoparticle suspension was added dropwise to the KH570 solution at a volume ratio of 1:5-1:10, and the mixture was stirred at room temperature for 2 hours;

[0038] After the reaction, the solvent was evaporated and dried at 70° C. for 2 hours.

[0039] Preferably, the application of the anti-slip coating comprises the following steps:

[0040] The anti-slip coating is evenly applied on the pre-treated tile surface by spraying, and the coating thickness is controlled at 200 microns;

[0041] The coating was dried at 150° C. for 2 hours.

[0042] Preferably, the surface property adjustment comprises the following steps:

[0043] Place the tiles, to which the anti-slip coating has been applied, under ultraviolet (UV) light;

[0044] The use intensity is 30mW / cm 2 Irradiation with UV light source;

[0045] The irradiation time was controlled to 1 hour.

[0046] The present invention also provides a nano-level super-anti-skid ceramic tile, which is prepared by the above method.

[0047] The key technology of the nano-scale super-anti-slip ceramic tile of the present invention is to achieve microstructure control and functionalization of the ceramic tile surface through innovative nanocomposite material design. These microstructures can provide a larger surface contact area and more friction points, significantly improving the anti-slip ability of the ceramic tile surface. The combination of cellulose nanocrystal (NCC) hydrogel and sodium polyacrylate (PAA) forms a porous network structure, which increases the surface roughness at the microscopic scale, thereby providing additional grip under wet conditions. At the same time, the introduction of polylactic acid (PLA) further enhances the mechanical stability and durability of the coating.

[0048] The surface modification of the nanoparticles was performed using gamma-methacrylate silane (KH570), a step that is critical as it allows the nanoparticles to be evenly dispersed in the hydrogel matrix and chemically bonded to the matrix, improving the overall stability of the coating. The nanoparticles include silica, alumina and titania, each with a unique role: silica and alumina provide additional wear resistance and a physical anti-slip structure, while titania introduces photocatalytic properties, giving the tile surface a self-cleaning function, which breaks down organic pollutants when exposed to light, reducing maintenance requirements.

[0049] The connection between these key technologies and their final effect is direct and clear. NCC and PAA provide the basic microscopic anti-slip structure, while the addition of PLA ensures the long-term stability of this structure. The modification and dispersion of nanoparticles ensure the uniformity and functionality of the coating, especially in terms of anti-slip and self-cleaning properties. This surface functionalization technology ensures that the safety of the tile is improved without sacrificing its appearance and feel.

[0050] In this invention, all key technologies do not exist in isolation, but are interrelated to form a synergistic system. The microstructure of NCC and PAA provides the basis for PLA, while PLA protects and enhances the stability of this structure. The surface modification and dispersion of nanoparticles enable this composite material to achieve the desired functions, which are ultimately reflected in the application of anti-slip coatings. The photocatalytic properties of titanium dioxide add a self-cleaning function to this new coating, reducing the need for long-term maintenance. This comprehensive technical solution optimizes the practicality, safety and economy of tiles, providing a new perspective to view and solve the anti-slip problem.

[0051] The technical solution provided by the embodiment of the present invention has the following beneficial effects:

[0052] By applying a mixture of cellulose nanocrystal hydrogel (NCC hydrogel) and sodium polyacrylate (PAA), as well as a composite system of polylactic acid (PLA) and specific nanoparticles, a unique micro-nanoscale surface structure is formed, which provides excellent anti-slip effect under wet and slippery conditions.

[0053] The surface modification of nanoparticles using γ-methacrylate silane (KH570) effectively improves the compatibility and stability of the nanoparticles in the coating, thereby ensuring the long-term durability of the coating and the persistence of the anti-slip effect.

[0054] The addition of titanium dioxide nanoparticles and subsequent ultraviolet (UV) irradiation treatment imparts photocatalytic properties to the tile surface, enabling a self-cleaning function that helps reduce the need for cleaning maintenance while providing continuous anti-slip protection BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 This is the SEM image of Example 1 of the present invention.

[0056] Figure 2 This is the SEM image of Comparative Example 2 of the present invention.

[0057] Figure 3 This is the SEM image of Comparative Example 3 of the present invention.

[0058] Figure 4 This is the SEM image of Comparative Example 5 of the present invention. DETAILED DESCRIPTION

[0059] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0060] Example 1

[0061] A method for preparing nano-level super-anti-slip tiles, the implementation steps are as follows:

[0062] S1) Preparation of tile substrate:

[0063] Mix clay, feldspar, quartz sand and kaolin in a weight ratio of 5:25:20:5, add 2 parts of iron oxide colorant and 3 parts of calcium carbonate enhancer,

[0064] The mixture was ground using a ball mill to a particle size of 80 μm.

[0065] By wet pressing, pressing in a hydraulic press,

[0066] The formed tiles were slowly dried in a drying room at 60°C for 12 hours.

[0067] The tiles are fired at 1150°C for 2 hours and then naturally cooled to room temperature in the kiln.

[0068] Use 400 grit sandpaper to sand the tile surface;

[0069] S2) Treatment of tile surface:

[0070] Use 5% NaOH solution to clean the tile surface.

[0071] Rinse thoroughly with deionized water and dry.

[0072] Dissolve γ-aminopropyltriethoxysilane (KH550) in ethanol at a volume percentage of 1%.

[0073] Evenly apply the above solution on the surface of the tile and dry it naturally at room temperature.

[0074] Heat curing at 100°C for 1 hour;

[0075] S3) Preparation of anti-slip coating:

[0076] NCC hydrogel with a solid content of 5% (w / w) and PAA solution with a solid content of 1% (w / w) were mixed at a solid content ratio of 1:1.

[0077] Adjust the pH of the mixture to 7.0,

[0078] Add 4% (w / w) PLA,

[0079] Add 1% (w / w) of nano-silicon dioxide particles and 1% (w / w) of nano-alumina particles,

[0080] The nanoparticles were surface modified with 0.1% (w / w) KH570.

[0081] Add 1.5% titanium dioxide nanoparticles (TiO2),

[0082] Cellulose nanocrystal hydrogel uses kexlan nanocellulose crystal NCC from Kaiyi New Materials Technology (Shanghai) Co., Ltd.; density is 1.27g / cm 3 , the width of NCC is 10nm, the length is 150nm, and the crystallinity is 85%;

[0083] The silicon dioxide nanoparticles have a particle size of 20 nanometers, the aluminum oxide nanoparticles have a particle size of 40 nanometers, and the titanium dioxide nanoparticles have a particle size of 20 nanometers.

[0084] The surface modification of nanoparticles in the anti-slip coating includes the following steps:

[0085] KH570 was added to isopropanol at a ratio of 0.1% (w / w);

[0086] Nano-silicon dioxide particles and nano-alumina particles are dispersed in deionized water at a ratio of 1% (w / w);

[0087] The above nanoparticle suspension was added dropwise to the KH570 solution at a volume ratio of 1:10, and the mixture was stirred at room temperature for 2 h;

[0088] After the reaction, the solvent was evaporated and dried at 70° C. for 2 hours.

[0089] S4) Application of anti-slip coating

[0090] The prepared anti-slip coating is evenly applied to the surface of the tile by spraying, and the coating thickness is about 200 microns.

[0091] Dry the coating at 150°C for 2 hours;

[0092] S5) Surface properties adjustment

[0093] Place the tiles with anti-slip coating under UV light.

[0094] Use 30mW / cm 2 The UV light source was irradiated for 1 hour.

[0095] Example 2

[0096] The same preparation method as in Example 1 was followed, except that cellulose nanocrystal hydrogel (NCC hydrogel) with a solid content of 1% (w / w) was used.

[0097] Example 3

[0098] The same preparation method as in Example 1 was followed, except that cellulose nanocrystal hydrogel (NCC hydrogel) with a solid content of 6% (w / w) was used.

[0099] Example 4

[0100] The same preparation method as in Example 1 was followed, except that 2% (w / w) of polylactic acid (PLA) was added.

[0101] Example 5

[0102] The same preparation method as in Example 1 was followed, except that 6% (w / w) of polylactic acid (PLA) was added.

[0103] Example 6

[0104] The same preparation method as in Example 1 was followed, except that 0.5% (w / w) of nano-silicon dioxide particles and 0.5% (w / w) of nano-alumina particles were added.

[0105] Example 7

[0106] The same preparation method as in Example 1 was followed, except that 1.5% (w / w) of nano-silicon dioxide particles and 1.5% (w / w) of nano-alumina particles were added.

[0107] Example 8

[0108] The same preparation method as in Example 1 is used, except that the silica nanoparticles used have a particle size of 10 nanometers and the alumina nanoparticles have a particle size of 30 nanometers.

[0109] Example 9

[0110] The same preparation method as in Example 1 is used, except that the silica nanoparticles used have a particle size of 30 nanometers and the alumina nanoparticles have a particle size of 50 nanometers.

[0111] Example 10

[0112] A method for preparing nano-level super-anti-slip tiles, the implementation steps are as follows:

[0113] S1) Preparation of tile substrate:

[0114] Mix clay, feldspar, quartz sand and kaolin in a weight ratio of 5:25:20:5, add 2 parts of iron oxide colorant and 3 parts of calcium carbonate enhancer,

[0115] The mixture was ground using a ball mill to a particle size of 50 μm.

[0116] By wet pressing, pressing in a hydraulic press,

[0117] The formed tiles were slowly dried in a drying room at 60°C for 12 hours.

[0118] The tiles are fired at 1150°C for 2 hours and then naturally cooled to room temperature in the kiln.

[0119] Use 400 grit sandpaper to sand the tile surface;

[0120] S2) Treatment of tile surface:

[0121] Use 5% NaOH solution to clean the tile surface.

[0122] Rinse thoroughly with deionized water and dry.

[0123] Dissolve γ-aminopropyltriethoxysilane (KH550) in ethanol at a volume percentage of 0.5%.

[0124] Evenly apply the above solution on the surface of the tile and dry it naturally at room temperature.

[0125] Heat curing at 100°C for 1 hour;

[0126] S3) Preparation of anti-slip coating:

[0127] NCC hydrogel with a solid content of 1% (w / w) and PAA solution with a solid content of 0.5% (w / w) were mixed at a solid content ratio of 1:1.

[0128] Adjust the pH of the mixture to 7.0,

[0129] Add 2% (w / w) PLA,

[0130] Add 0.5% (w / w) of nano-silicon dioxide particles and 0.5% (w / w) of nano-alumina particles,

[0131] The nanoparticles were surface modified with 0.1% (w / w) KH570.

[0132] Add 0.5% titanium dioxide nanoparticles (TiO2),

[0133] Cellulose nanocrystal hydrogel uses kexlan nanocellulose crystal NCC from Kaiyi New Materials Technology (Shanghai) Co., Ltd.; density is 1.27g / cm 3 , the width of NCC is 10nm, the length is 150nm, and the crystallinity is 85%;

[0134] The silicon dioxide nanoparticles have a particle size of 10 nanometers, the aluminum oxide nanoparticles have a particle size of 30 nanometers, and the titanium dioxide nanoparticles have a particle size of 10 nanometers.

[0135] The surface modification of nanoparticles in the anti-slip coating includes the following steps:

[0136] KH570 was added to isopropanol at a ratio of 0.1% (w / w);

[0137] Nano-silicon dioxide particles and nano-alumina particles are dispersed in deionized water at a ratio of 1% (w / w);

[0138] The above nanoparticle suspension was added dropwise to the KH570 solution at a volume ratio of 1:5, and the mixture was stirred at room temperature for 2 h;

[0139] After the reaction, the solvent was evaporated and dried at 70° C. for 2 hours.

[0140] S4) Application of anti-slip coating

[0141] The prepared anti-slip coating is evenly applied to the surface of the tile by spraying, and the coating thickness is about 200 microns.

[0142] Dry the coating at 150°C for 2 hours;

[0143] S5) Surface properties adjustment

[0144] Place the tiles with anti-slip coating under UV light.

[0145] Use 30mW / cm 2 The UV light source was irradiated for 1 hour.

[0146] Embodiment 11

[0147] A method for preparing nano-level super-anti-slip tiles, the implementation steps are as follows:

[0148] S1) Preparation of tile substrate:

[0149] Mix clay, feldspar, quartz sand and kaolin in a weight ratio of 5:25:20:5, add 2 parts of iron oxide colorant and 3 parts of calcium carbonate enhancer,

[0150] The mixture was ground using a ball mill to a particle size of 100 μm.

[0151] By wet pressing, pressing in a hydraulic press,

[0152] The formed tiles were slowly dried in a drying room at 60°C for 12 hours.

[0153] The tiles are fired at 1150°C for 2 hours and then naturally cooled to room temperature in the kiln.

[0154] Use 400 grit sandpaper to sand the tile surface;

[0155] S2) Treatment of tile surface:

[0156] Use 5% NaOH solution to clean the tile surface.

[0157] Rinse thoroughly with deionized water and dry.

[0158] Dissolve γ-aminopropyltriethoxysilane (KH550) in ethanol at a volume percentage of 1%.

[0159] Evenly apply the above solution on the surface of the tile and dry it naturally at room temperature.

[0160] Heat curing at 100°C for 1 hour;

[0161] S3) Preparation of anti-slip coating:

[0162] NCC hydrogel with a solid content of 6% (w / w) and PAA solution with a solid content of 1.5% (w / w) were mixed at a solid content ratio of 1:1.

[0163] Adjust the pH of the mixture to 7.0,

[0164] Add 6% (w / w) PLA,

[0165] Add 1.5% (w / w) of nano-silicon dioxide particles and 1.5% (w / w) of nano-alumina particles,

[0166] The nanoparticles were surface modified with 0.1% (w / w) KH570.

[0167] Add 2% titanium dioxide nanoparticles (TiO2),

[0168] Cellulose nanocrystal hydrogel uses kexlan nanocellulose crystal NCC from Kaiyi New Materials Technology (Shanghai) Co., Ltd.; density is 1.27g / cm 3 , the width of NCC is 10nm, the length is 150nm, and the crystallinity is 85%;

[0169] The silicon dioxide nanoparticles have a particle size of 30 nanometers, the aluminum oxide nanoparticles have a particle size of 50 nanometers, and the titanium dioxide nanoparticles have a particle size of 30 nanometers.

[0170] The surface modification of nanoparticles in the anti-slip coating includes the following steps:

[0171] KH570 was added to isopropanol at a ratio of 0.1% (w / w);

[0172] Nano-silicon dioxide particles and nano-alumina particles are dispersed in deionized water at a ratio of 1% (w / w);

[0173] The above nanoparticle suspension was added dropwise to the KH570 solution at a volume ratio of 1:10, and the mixture was stirred at room temperature for 2 h;

[0174] After the reaction, the solvent was evaporated and dried at 70° C. for 2 hours.

[0175] S4) Application of anti-slip coating

[0176] The prepared anti-slip coating is evenly applied to the surface of the tile by spraying, and the coating thickness is about 200 microns.

[0177] Dry the coating at 150°C for 2 hours;

[0178] S5) Surface properties adjustment

[0179] Place the tiles with anti-slip coating under UV light.

[0180] Use 30mW / cm 2 The UV light source was irradiated for 1 hour.

[0181] Comparative Example 1

[0182] The same preparation method as in Example 1 was followed, except that no coating layer was used.

[0183] Comparative Example 2

[0184] The same preparation method as in Example 1 was followed, except that the silica nanoparticles and the alumina nanoparticles were not added.

[0185] Comparative Example 3

[0186] The same preparation method as in Example 1 was used, except that the surface of the nanoparticles in the anti-slip coating was not modified.

[0187] Comparative Example 4

[0188] The same preparation method as in Example 1 was followed, except that polylactic acid (PLA) was not added.

[0189] Comparative Example 5

[0190] The same preparation method as in Example 1 was followed, except that the tile surface was not treated.

[0191] Experimental test:

[0192] 1. Anti-slip performance test:

[0193] According to the standard GB / T 4100-2015 "Ceramic Tiles",

[0194] Sliding distance: 25cm; Sliding time: 3s

[0195] 2. Wear test,

[0196] According to GB / T 3810.6-2016 "Test method for wear resistance of ceramic tiles"

[0197] Load: (30±2)N; Wear cycle number: 10000 times

[0198] 3. Adhesion strength test,

[0199] According to GB / T 5210-2006 "Cross-cut test for adhesion of paints and varnishes"

[0200] Cutting distance: 1mm

[0201] Table 1 Experimental data

[0202]

[0203] Example 1: shows the best comprehensive performance, with the highest dynamic coefficient of friction (DCOF), the smallest wear depth and mass loss, and the best adhesion strength. This shows that the optimized combination of all ingredients and steps in Example 1 provides excellent anti-slip performance and durability.

[0204] Examples 2-9: Although they have different performances, they all show relatively excellent performance, especially in terms of dynamic friction coefficient and adhesion strength level. These examples show how fine-tuning the proportion of each component in the preparation method affects the performance of the final product.

[0205] Compared with the optimal embodiment 1, the dynamic friction coefficient of embodiments 2 and 3 is slightly decreased, which is because the change of the NCC hydrogel content affects the anti-slip performance of the coating.

[0206] The adhesion strength ratings for Examples 4 and 5 decreased slightly because the PLA content had an effect on the bond strength between the coating and the tile substrate.

[0207] The wear depth and mass loss of Examples 6-9 are relatively high, indicating that the content and particle size of nanoparticles affect the wear resistance of the coating.

[0208] Comparative Examples 1-5: showed poor performance, especially in the dynamic friction coefficient and wear test. These comparative examples demonstrate that the components and processing steps selected in the examples are essential for achieving high performance anti-slip tiles.

[0209] Comparative Example 1 shows that the tile without coating has the worst performance in the dynamic friction coefficient and wear tests, indicating that the anti-slip coating is essential to improve the anti-slip performance of the tile.

[0210] Comparative Examples 2-5 provide data on tile performance without specific treatments or components, and the results show that these components and treatment steps are necessary to ensure integrity and optimization of product performance.

[0211] from Figure 1-4 It can be seen that the relatively regular distribution of nanoparticles in Example 1 shows good dispersibility and uniformity. The lack of silicon dioxide and aluminum oxide nanoparticles significantly affects the structure and performance of the coating, resulting in reduced anti-skid performance and wear resistance. The lack of surface modification treatment leads to poor compatibility and stability of the nanoparticles in the coating, and the surface is not treated, which affects the long-term stability and anti-skid effect of the coating.

[0212] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing nano-level super-anti-slip tiles, characterized in that: The following steps are involved: S1) Preparation of ceramic tile substrate; S2) Treatment of tile surface; S3) Preparation of anti-slip coating; S4) Application of anti-slip coating; S5) Surface property adjustment.

2. The method for preparing super non-slip tiles according to claim 1, characterized in that: The preparation of the ceramic tile substrate comprises the following steps: Clay, feldspar, quartz sand and kaolin are mixed in a weight ratio of 5 parts, 25 parts, 20 parts and 5 parts, wherein 2 parts of iron oxide colorant and 3 parts of calcium carbonate reinforcing agent are added; The mixture was ground into a particle size of 50-100 μm using a ball mill; The wet pressing method is adopted, and the pressing is carried out in a hydraulic press; The formed tiles were slowly dried in a drying room at 60°C for 12 hours; The dried tiles were sintered at 1150°C for 2 hours; After firing is complete, allow the tiles to cool naturally to room temperature in the kiln; Use 400 grit sandpaper to sand the tile surface.

3. The method for preparing nano-level super-anti-slip tiles according to claim 1, characterized in that: The treatment of the tile surface comprises the following steps: Use 5% NaOH solution to clean the tile surface; Rinse the cleaned tile surface with deionized water and dry it; Dissolve γ-aminopropyltriethoxysilane (KH550) in ethanol at a volume percentage of 0.5%-1%; Evenly apply the above solution on the surface of the tile and dry it naturally at room temperature; The coated tile surface was heat cured at 100°C for 1 hour.

4. The method for preparing nano-level super-anti-slip tiles according to claim 1, characterized in that: The preparation of the anti-slip coating comprises the following steps: A cellulose nanocrystal hydrogel (NCC hydrogel) having a solid content of 1-6% (w / w) and a sodium polyacrylate (PAA) solution having a solid content of 0.5-1.5% (w / w) were mixed at a solid content ratio of 1:1; Adjusting the pH of the mixture to 7.0; Adding 2-6% (w / w) polylactic acid (PLA) to the pH-adjusted mixture; Adding 0.5-1.5% (w / w) of nano silicon dioxide particles and 0.5-1.5% (w / w) of nano aluminum oxide particles; The nanoparticles were surface modified using 0.1% (w / w) of γ-methacrylate silane (KH570) to improve their compatibility and dispersibility in the hydrogel; 0.5-2% (w / w) of titanium dioxide nanoparticles (TiO2) were added to the mixture.

5. The method for preparing nano-level super-anti-slip tiles according to claim 4, characterized in that: The silicon dioxide nanoparticles have a particle size of 10-30 nanometers, the aluminum oxide nanoparticles have a particle size of 30-50 nanometers, and the titanium dioxide nanoparticles have a particle size of 10-30 nanometers.

6. The method for preparing nano-level super-anti-slip tiles according to claim 4, characterized in that: The surface modification of the nanoparticles in the anti-slip coating comprises the following steps: KH570 was added to isopropanol at a ratio of 0.1% (w / w); Nano-silicon dioxide particles and nano-alumina particles are dispersed in deionized water at a ratio of 1% (w / w); The above nanoparticle suspension was added dropwise to the KH570 solution at a volume ratio of 1:5-1:10, and the mixture was stirred at room temperature for 2 hours; After the reaction, the solvent was evaporated and dried at 70° C. for 2 hours.

7. The method for preparing nano-level super-anti-slip tiles according to claim 1, characterized in that: The application of the anti-slip coating comprises the following steps: The anti-slip coating is evenly applied on the pre-treated tile surface by spraying, and the coating thickness is controlled at 200 microns; The coating was dried at 150° C. for 2 hours.

8. The method for preparing nano-level super-anti-slip tiles according to claim 1, characterized in that: The surface property adjustment comprises the following steps: Place the tiles, to which the anti-slip coating has been applied, under ultraviolet (UV) light; The use intensity is 30mW / cm 2 Irradiation with UV light source; The irradiation time was controlled to 1 hour.

9. A nano-level super-anti-slip tile, characterized in that: The anti-slip ceramic tile is prepared according to any one of claims 1-9.

Citation Information

Patent Citations

  • Ceramic tile having antiskid effect and manufacturing method thereof

    CN104261897A

  • Tile with high whole body whiteness

    CN105330256A

  • Development and application of multifunctional polymer-based clean surface antiskid technology

    CN112251142A

  • Antifouling lightweight ceramic tile and preparation method thereof

    CN117069476A

  • Super-antiskid multifunctional ceramic tile and preparation method thereof

    CN117658614A

Cited By

  • Preparation method of anti-skid and antibacterial ceramic tile and anti-skid and antibacterial ceramic tile

    CN119931426A